2022
DOI: 10.2903/j.efsa.2022.7311
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of listing and categorisation of animal diseases within the framework of the Animal Health Law (Regulation (EU) No 2016/429): antimicrobial‐resistant Escherichia coli in dogs and cats, horses, swine, poultry, cattle, sheep and goats

Abstract: Escherichia coli ( E. coli ) was identified among the most relevant antimicrobial‐resistant (AMR) bacteria in the EU for dogs and cats, horses, swine, poultry, cattle, sheep and goats in previous scientific opinions. Thus, it has been assessed according to the criteria of the Animal Health Law (AHL), in particular criteria of Article 7 on disease profile and impacts, Article 5 on its eligibility to be listed, Annex IV for its categorisation according to disease prevention and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 169 publications
0
9
0
Order By: Relevance
“…Therefore, this review is focused on ETEC due to its high pathogenicity in porcine, being the one responsible for the most cases, in number and severity, of swine enteric colibacillosis. Besides that, ETEC was classified as the most important multi-drug resistant (MDR) bacteria in pig production by the European Food Safety Authority (EFSA) [ 7 ]. Hence, in the following subchapter, the mechanisms of virulence and the pathogenesis for ETEC are detailed.…”
Section: Etiologymentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, this review is focused on ETEC due to its high pathogenicity in porcine, being the one responsible for the most cases, in number and severity, of swine enteric colibacillosis. Besides that, ETEC was classified as the most important multi-drug resistant (MDR) bacteria in pig production by the European Food Safety Authority (EFSA) [ 7 ]. Hence, in the following subchapter, the mechanisms of virulence and the pathogenesis for ETEC are detailed.…”
Section: Etiologymentioning
confidence: 99%
“…E. coli is both a harmless commensal bacterium in the intestines of several mammals, as well as a dangerous pathogen [ 5 ]. Still, a small proportion of strains are pathogenic and can cause severe to life-threatening intestinal and extra-intestinal infections in humans and animals [ 5 , 7 , 8 , 9 , 10 ]. The pathogenicity of the strains is characterized by the presence of certain virulence factor combinations in particular adhesins and toxin secretions.…”
Section: Etiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Resistance is problematic in many pathogens and commensals of canine origin, including staphylococci, enterococci, Escherichia coli , and Salmonella [ 5 , 6 , 7 ]. For instance, in a study performed by Elnageh et al [ 8 ], 13 out of 38 staphylococci isolated from 151 pets were identified as methicillin-resistant.…”
Section: Introductionmentioning
confidence: 99%